Assessment of Odonate Diversity in Pandharkawada Forest Division of Maharashtra, India: Habitat Dynamics and Conservation Implications - Ramzan Virani; Sarita Kawade (The Bioscan, 2025)
This study investigates the diversity and distribution of Odonates across varied habitats in the Pandharkawada Forest Division, Maharashtra, India, focusing on wetlands, forest land, agricultural land, and urban areas. Odonates serve as bioindicators, making their diversity crucial for assessing ecosystem health. Wetlands in the division, though ecologically significant, are under threat from biotic pressures such as commercial fishing and domestic use, leading to habitat degradation. Saikheda Dam exhibited the highest Odonate diversity (H' = 1.37), followed closely by Muchi Dam (H' = 1.368) and Wai Dam (H' = 1.361). Forest habitats also supported a rich Odonate population, with Transect V (riverine area) showing the highest diversity (H' = 1.378). Agricultural lands adjacent to forest areas supported diverse populations, with wetland transects being the most diverse (H' = 1.384). However, urbanization and agricultural expansion threaten Odonate diversity through habitat loss, pollution, and pesticide use. The study highlights the critical role of wetlands and forested areas in sustaining Odonate diversity and emphasizes the need for conservation measures to mitigate the impacts of human activities. Continued monitoring and habitat restoration efforts are essential for preserving Odonate populations and maintaining the ecological balance in the region.